(untitled) (Research, Society and Development, 2020)
When talking about rural youth, many works address the family succession process and life expectations within the rural environment. Thus, it is necessary to analyze how young people living in a “rural” context define themselves and perceive themselves as situated in their own historical context and with specific problems. The present work aims to understand how the perceptions, experiences and social representations of young people who live in agricultural settlements in the Zona da Mata de Alagoas about family farming and the processes of socialization in the fields of education, work, family and political activity. To collect data, questionnaires were used with thirty-two young people who lived in the settlements. Thus, we realize that there is a low prospect of increased schooling and income production in rural areas, which is in conflict with the desire of these young people to remain in their community. It was evident that the majority likes to live in the rural community and participate in work in the field; as well as a large percentage of those who intend to continue their parents’ work in the settlements and continue to live in them. Participation in associations and cooperatives is low, but in social movements it is more representative. In addition to the desire to remain in the rural environment, there is a great expectation of achieving the permanent objectives in the settlements.